Effect of clinical hyperthyroidism and hypothyroidism on patent diabetes. 59 cases - Hirbli, K. (1983)
Fifty-nine patients with both clinical evidence of thyroid dysfunction and patent diabetes mellitus were investigated in our diabetology department. Patients with euthyroid goitre and iatrogenic or pituitary hypothyroidism were excluded from the study. Among the 45 diabetics with hyperthyroidism, 32 had Graves' disease and 13 had toxic adenoma; 71% were insulin-treated. Hyperthyroidism had passed unnoticed in 7 of these 32 patients because fatigue and loss of weight, which initially were the predominant or sole symptoms, are extremely frequent in uncontrolled diabetes. These symptoms, as well as polyuria, polyphagia and even sweating are common to both diseases. Considerable deterioration in the control of glycaemia was observed in 63% of the insulin-treated patients when hyperthyroidism developed, with a 17 to 212% (mean 82%) increase in insulin dosage in 53%. There was no correlation between the degree of hyperthyroidism and the loss of control. Following treatment of the hyperthyroidism, control was improved in 63%, with an 11-83% (mean 44%) decrease in insulin dosage in 59% of them. Insulin therapy could be withdrawn in only one of the 32 insulin-treated patients. Non-iatrogenic primary hypothyroidism was found in 0.2% of the diabetics investigated. This incidence was significantly higher than the calculated probability of the two diseases occurring by chance in the same patient. Eleven out of 14 patients were insulin-treated. When hypothyroidism developed, 73% of them had their insulin dosage reduced, with a high frequency of hypoglycaemic disorders: repeated "malaise" in 55% and coma in 27%. A higher proportion of vitiligo was also noted: 14% in the total patient population reported, and 18% in insulin-treated patients.